2014
DOI: 10.1007/s11270-014-2186-4
|View full text |Cite
|
Sign up to set email alerts
|

The Air Quality in African Rural Environments. Preliminary Implications for Health: The Case of Respiratory Disease in the Northern Benin

Abstract: Recently, the World Health Organization's International Association for Research on Cancer classified outdoor air pollution as carcinogenic to humans and puts air pollution in the same category as tobacco smoke, UV radiation, and plutonium. The ambient air is polluted by emissions from motor vehicles, industrial processes, power generation, household combustion of solid fuel, and other sources. Dust storms lead to particulate levels that exceed internationally recommended levels, especially near the Sahara. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…They found that people who experienced prolonged exposure to particulates had a high prevalence of impaired lung function. De Longueville et al [17] took respiratory diseases in northern Benin as an example to explore the initial effect of air quality on health in rural Africa, and to evaluate the real impact of Sahara dust on air quality and the respiratory health of children in West Africa. In a rural area in central Greece, Kelepertzis [18] investigated the possible effects of human activities on the metal loading of surface soils and the possible effect on the chemical quality of tap water in surrounding villages.…”
Section: Introductionmentioning
confidence: 99%
“…They found that people who experienced prolonged exposure to particulates had a high prevalence of impaired lung function. De Longueville et al [17] took respiratory diseases in northern Benin as an example to explore the initial effect of air quality on health in rural Africa, and to evaluate the real impact of Sahara dust on air quality and the respiratory health of children in West Africa. In a rural area in central Greece, Kelepertzis [18] investigated the possible effects of human activities on the metal loading of surface soils and the possible effect on the chemical quality of tap water in surrounding villages.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that fine particles deteriorate urban air quality and endanger human health and the ecosystem because they have the characteristics of long-term residence in the air, small grain size, large specific surface area and the ability to accumulate hazardous substances, etc [1]. The International Agency for Research on Cancer (IARC), an important agency of the World Health Organization (WHO), has issued a report showing that atmospheric pollution is a common and primary environmental carcinogen and humans can suffer from lung cancer after living in polluted air for a long time [2,3]. The results of epidemiological studies, both at home and abroad, have shown that fine particles can have a severe effect on the human body, such as the respiratory system, nervous system, immune system and the genome [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…F 0.05(1,2)=18.51. According to table 6, it is known that the three factors and the interactions z 1 z 2 and z 1 z 3 have a distinct influence in the experiment, so the regression equation established is also distinct.F 0.01 (1,2)=98.50.…”
mentioning
confidence: 98%